2015
DOI: 10.1016/j.jssr.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reading Instruction on Learning Outcomes in Social Studies: A Synthesis of Quantitative Research

Abstract: Quantitative research studies examining the effects of literacy instruction set in social studies classrooms (grades 6-12) on students’ academic content learning and reading comprehension are synthesized using meta-analytic techniques. An extensive search of the scholarly literature between 1983 and 2013 yielded a total of twelve intervention studies that provided literacy instruction to secondary students within social studies classes and quantitatively measured content learning outcomes, reading comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Students' understanding and comprehension in social studies increase when they make connections between prior knowledge and new knowledge being studied (McCulley and Osman, 2015). However, teaching students to connect material and knowledge they have already been taught combined with new material and content from texts is easier when they already have strong reading comprehension skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' understanding and comprehension in social studies increase when they make connections between prior knowledge and new knowledge being studied (McCulley and Osman, 2015). However, teaching students to connect material and knowledge they have already been taught combined with new material and content from texts is easier when they already have strong reading comprehension skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies show that the use of summarizing strategy affects reading comprehension and through reading comprehension also students' learning achievement in both very young and older students Marzano, Pickering, & Pollock 2001;McCulley & Osman, 2015;Kolić-Vehovec, Bajšanski, & Rončević Zubković, 2011). Students who understood the text well included more first level statements in their summaries compared to students who did not understand the text well.…”
Section: Reading Comprehension and Summarizing Skillmentioning
confidence: 99%
“…Alanyazında, sosyal bilgiler öğretim programına ilişkin görüşlerin belirlendiği (Doğanay & Sarı, 2008;Gültekin, Gürdoğan-Bayır & Göz, 2004;Yapıcı & Demirdelen, 2007), sosyal bilgiler dersinde belirlenen bir öğrenme alanındaki kazanımların ele alındığı (Çakmak & Taşkıran, 2015), sosyal bilgiler kazanımlarının taksonomik açıdan değerlendirildiği (Demir, 2015;Gazel & Erol, 2012), birçok araştırmada da uygulanan farklı öğretim yaklaşımlarının sosyal bilgilerdeki kazanımlara etkisinin ortaya konulduğu (Gloria & Afolabi, 2013;Gültekin, 2005;McCulley & Osman, 2015), farklı yıllarda uygulamaya konulmuş sosyal bilgiler öğretim programı kazanımlarının karşılaştırıldığı (Okta, 2008) araştırmalar bulunduğu ortaya çıkmıştır. Oysa sosyal bilgiler öğretim programı kazanımlarına ilişkin yaşanan sorunların belirlenmeye çalışıldığı bir araştırmaya rastlanmamıştır.…”
Section: Türkçe Sürüm Girişunclassified
“…In the literature, there are studies that determine the views on the social studies curriculum (Doğanay & Sarı, 2008;Gültekin, Gürdoğan-Bayır & Göz, 2004;Yapıcı & Demirdelen, 2007), focus on the outcomes in a learning domain within the social studies course (Çakmak & Taşkıran, 2015), evaluate the social studies outcomes taxonomically (Demir, 2015;Gazel & Erol, 2012), report the effect of different instructional approaches on the outcomes in the social studies course (Gloria & Afolabi, 2013;Gültekin, 2005;McCulley & Osman, 2015), and compare the outcomes implemented in different periods (Okta, 2008). However, no studies have been found determining the problems encountered with regard to the outcomes of the social studies curriculum.…”
Section: Introductionmentioning
confidence: 99%